Perceptions of service quality at football stadiums: influence on fans’ intention to attend future games - Chanchai Phonthanukitithaworn (2019)
© 2018, © 2018 Informa UK Limited, trading as Taylor & Francis Group. This study enhances the understanding of service quality at major spectator sports events in Thailand by examining the relationship between spectators’ perception of event quality and their behavioral intention to attend future games. Structural equation modeling (SEM) is used to analyze data collected from 849 spectators who attended Thai Premier League (TPL) games at three major stadiums in Bangkok. The empirical results indicate that spectator satisfaction and aesthetic quality associated with game-day attendance directly affect behavioral intention to attend future events. Notably, team performance (denoted as outcome quality) and total attendance cost were found to significantly influence spectators’ satisfaction and behavioral intention to attend future games. The study contributes substantially to the literature by proposing a model with four dimensions that directly affect the important issues of consumer satisfaction and subsequent intention to re-attend an event. Thai cultural features such as collectivism, a long-term outlook, and feminism are argued as being aligned with the proposed model dimensions. We discuss some of the findings with respect to these cultural features. Furthermore, the proposed total attendance cost dimension is novel in that it includes both monetary and non-monetary costs.